Reconstructing the Rights to Justice and Legal Protection for Disabled Youth in the Frame of Human Rights - Guntara, Peter; Dewi, Seroja Kusuma; Handayani, Rini DP (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Adolescents with disabilities often receive discriminatory treatment and are far from a sense of justice. This causes adolescents with disabilities to experience limitations in fulfilling the rights that they should get. Disabled adolescents basically have the same rights as non-disabled adolescents in general. All forms of rights attached to adolescents with disabilities have been fully compiled in the concept of Human Rights. The government's seriousness in fulfilling the rights of adolescents with disabilities has been compiled with the ratification of the Convention on the Rights of Persons with Disabilities into Law Number 19 of 2011. In addition, the government has also promulgated Law Number 8 of 2016 concerning Persons with Disabilities. This research is descriptive qualitative research using an empirical normative approach. This research discusses the importance of fulfilling the rights of justice and legal protection for adolescents with disabilities by putting forward the theory of justice based on human rights. Through a complete understanding of the concept of justice rights and legal protection for adolescents with disabilities, it is hoped that discriminatory actions against adolescents with disabilities will never reappear and can restore the rights of all adolescents with disabilities. Based on the results of the study, a new concept of ideas related to the reconstruction of justice rights and legal protection for youth with disabilities in Indonesia based on positive law and human rights theory is obtained, namely with the ISPAS method approach (Issuance, Surveillance, Participation, Specifications).